Theranostic Gold Nanoshells: from Synthesis to Imaging and Photothermal Therapy Applications - Lien, Nghiem Thi Ha; Duong, Vu Thi Thuy; Duong, Vu; Hoa, Do Quang; Nhung, Tran Hong (Communications in Physics, 2014)
Gold nanoshells (GNSs) were grown on monodispersed aminoprotpyltriethoxysilane (APTES) functionalized of silica nanoparticles (NPs) cores with varying sizes ranging from 40-180 nm synthesized by Stober route. Gold shells were deposited onto the surface of silica NPs by tetrakis(hydroxymethyl) phosphonium chloride (THPC) and electroless gold plating method. The coverage of the gold nanoshells on the surfaces of the silica NPs was evaluated using UV-VIS/NIR spectrospcopy and transmission electron microscopy (TEM). The plasmon resonance wavelengths of these gold nanoshells were tunable from visible to near infrared region. The GNSs were also bioconjugated with anti-HER2 monoclonal antibody for diagnostic breast cancer cells using dark field microscope technique. These GNS NPs play a role as nanoheaters transforming light to heat. With the present of these GNS NPs at volume density of $3.6× 10^{10}$ NPs.cm$^3$ in chicken tissue samples, illuminated by 808 nm laser at the power density of 62~W.cm$^2$ the temperature of tissue sample reachs 110\rc{ }C after 20 minutes illumination